Dispersed-ply design and optimization to improve the brittle flexural behaviour of composite laminates. (January 2023) - Mouri Sardar Abadi, P.; Baluch, Abrar H.; Sebaey, T.A.; Peeters, D.; Barzegar, M.; Lopes, C.S.
Abstract: This work aims to improve the flexural behaviour of unidirectional fibre-reinforced laminates by means of coupling an optimization procedure for quasi-isotropic configurations with the design space opened by dispersed-ply orientations. The design approach consists of finding suitable alternatives to traditional laminates (with fibre orientations limited to 0°, ± 4 5 ∘, and 90°), while maintaining their stiffness characteristics. This strategy isolates the interlaminar response as the objective function that is optimized to improve their flexural behaviour. To this end, a modified Ant Colony Optimization was implemented and geared towards optimizing the interlaminar stress profile, allowing plies at every possible 5 ° orientation, with the ultimate goal of delaying delamination. To validate the approach, a traditional reference laminate and derived fully dispersed designs were experimentally tested. The correlated responses show that it was not possible to improve flexural resistance. However, the typical flexural brittleness of laminates can be modified into a pseudo-ductile behaviour.